Upaya Meningkatkan Keterampilan Menulis Aksara Jawa Melalui Model Kooperatif Tipe Round Table dengan Media Flashcard pada Siswa Kelas IV SD - Wenti Ferdina Fitrianti; Okto Wijayanti; Arifin Muslim (Universitas PGRI Semarang, 2019)
The background of this research was the poor ability of writing Javanese Alphabet in Javanese Language subject of the fourth grade students in SD N 1 Alasmalang. The purpose of this research was improving the ability of writing Javanese Alphabet through cooperative learning model of round table type using flashcard media. This classroom action research was conducted in two phases, which were cycle I and cycle II that included twice meetings in each cycle. The subject of this research were 20 students of the fourth grade students in SD N 1 Alasmalang in academic year 2018/2019, which consisted 11 males and 9 females. The instruments used were test and non-test. The classroom action research that was proposed by Kemmis and Mc Taggart involved planning, implementing, observing, and reflecting. The observation result in the learning process of cycle I and cycle II showed that the students’ ability of writing Javanese Alphabet was improved. The result of the cycle 1 achieved 59,5% with enough criteria and the cycle II was improved into 80% with good criteria. The students’ ability of writing Javanese Alphabet had achieved the indicator of success that was determined with good criteria at least 75% from the minimum criteria of mastery learning (KKM), which was 70. From the findings, it can be concluded that Round Table using flashcard media was able to improve the ability of writing Javanese alphabhet.